Menschen zählen Wissensproduktion durch britische Volkszählungen und Umfragen vom 19. Jahrhundert bis ins digitale Zeitalter - Brückweh, Kerstin (Veröffentlichungen des Deutschen Historischen Instituts London/ Publications of the German Historical Institute London, 2015)
This book gets to the heart of discussions on big data and the digital age. It presents the 200-year history of the idea that people and societies are nothing more than the sum total of the data collected by quantitative methodology. It describes this history in the context of censuses and survey research in Great Britain, focusing on the actors involved, methodology, social classifications, and questions about race, ethnicity and disabilities.